PENGARUH DISIPLIN KERJA, KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN (Studi Kasus Pada PT Batang Hari Bengkulu Pratama) - Prayogi Permadi; Merta Kusuma ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2021)
This study aims to know the effect of work discipline, compensation and work motivation on employee performance at PT. Batanghari Bengkulu Pratama, either partially or simultaneously. There are several factors that are discussed in this study, namely work discipline, compensation and work motivation. The object of this research is 100 employees at PT. Batanghari Bengkulu Pratama. In this research, the researcher used data collection methods by means of observation, interviews and distributing questionnaires. There are several data analysis techniques used in this study, among other are by using instrument test, classical assumption test, respondent response analysis, multiple linear regression analysis, determinant coefficient, and hypothesis testing. From the results of the tests that have been carried out, it can be concluded that the variables of Work Discipline (X1), Compensation (X2) and Work Motivation (X3)partially or simultaneously have an effect on Employee Performance at PT. Batanghari Bengkulu Pratama. The t-test results for the Work Discipline variable (X1) show the value of tcount >ttabel (Î±/2) (2.232> 1.98498) and (sig < Î± = 0.028 <0.050), the variable compensation (X2) shows the value of tcount >ttabel(Î±/2) (2.399> 1.98498) and (sig < Î± = 0.018 <0.050), Work Motivation Variable (X3) shows the value of tcount >ttable (Î±/2) (3.257> 1.98498) and (sig < Î± = 0.002 <0.050). In addition, from the results of the multiple linear regression test, the regression equation is obtained as follows: Y = 5.030 + 0.250 (X1) + 0.374 (X2) + 0.837 (X3)Â Keywords: Work Discipline, Compensation, Work Motivation and Employee Performance